Generalizability of Homeopathic Prognostic Factor Research Outcome in COVID-19 Treatment: Comparison of Data - Rutten, Lex; Miglani, Anjali; Gold, Peter; Manchanda, Raj Kumar; Chakraborty, Moumita; Meena, Baljeet Singh; Sharma, Kavita; Gupta, Meeta; Sharma, Brender; Sharma, Ashok; Rani, Purnima; Singh, Rahul Kumar (Homeopathy, 2021)
Background/Objective During the coronavirus disease 2019 (COVID-19) pandemic, several homeopathic prognostic factor research (PFR) projects have been undertaken. We found two projects with comparable outcomes to assess consistency and possible flaws.Methods Two comparisons were made. (1) Outcome of a PFR data collection from the Liga Medicorum Homoeopathica Internationalis (LMHI) by about 100 doctors with 541 cases was compared with a previous analysis of 161 cases in the same database. (2) The updated LMHI database was also compared with a data collection carried out in India by four doctors with a total of 1,445 cases. Differences that resulted in conflicting outcomes (indication in one, contraindication in the other) were examined for possible causes.Results There was only a single outcome in the updated LMHI database that conflicted with the previous dataset, and this could have been due to statistical variation. The Indian data contained many cases, from few doctors, while the LMHI database had few cases per doctor, but many doctors. The overlap between the projects (individual cases entered in both) was between zero and 22%. In 72 comparisons we found six (8.3%) conflicting outcomes. Possible causes were statistical error due to small numbers of cases and/or observers, confirmation bias, and keynote prescribing if this resulted in symptoms being inadequately checked.Conclusion There was little conflict between the outcomes of the two versions of one project and between the two different PFR projects. Differences could mostly be explained by causes that can be managed. This consistency should primarily be interpreted as showing a strong overall consensus between homeopathic practitioners worldwide, but with variation of consensus between small groups of practitioners.
Keywords: COVID-19; homeopathy; prognostic factor research; likelihood ratio; consensus